Respiratory insufficiency in an infant with osteogenesis imperfecta - Adeline Yi Ling Lim; Ajay Kevat (Respiratory Medicine Case Reports)
Osteogenesis imperfecta (OI) is a rare presentation in the pediatric population. Whilst orthopedic manifestations are well-publicised, the multiple respiratory complications and mechanisms of respiratory failure in more severe cases are less well described. We report the clinical, radiological and histopathological details of the case of an infant with genetically-confirmed OI (Type 2) and associated respiratory insufficiency, as well as summarise the relevant existing literature. This case highlights the importance of the recognition of clinical challenges associated with the management of respiratory complications in a patient with OI.